EFEKTIVITAS EFEKTIVITAS PEKERJAAN DAN SUPERVISI ARSIP UNTUK MENINGKATKAN KUALITAS LAYANAN PERPUSTAKAAN DI SMP NEGERI 46 PALEMBANG: EFEKTIVITAS PEKERJAAN DAN SUPERVISI ARSIP UNTUK MENINGKATKAN KUALITAS LAYANAN PERPUSTAKAAN DI SMP NEGERI 46 PALEMBANG - Nikko, Nikko; Situmorang , Tonny P; Ridho, Hatta (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political UMA), 2025)
This study examines the social life and political behavior of Chinese Muslim communities in Medan City during the 2019 Indonesian General Election. Using a qualitative descriptive approach, data were collected through in-depth interviews, observation, and documentation. The findings show that Chinese Muslims construct a dual identity as an ethnic minority and religious adherents of Islam, which is negotiated contextually within family, ethnic, and broader Muslim communities. This dual positioning shapes their social interactions and political orientations. In the 2019 election, Chinese Muslims demonstrated relatively high levels of political participation, primarily through voting and informal political discussions. Their political preferences were influenced more by candidates’ track records, leadership capacity, and commitment to social stability than by ethnic or religious affiliation. The study further identifies several typologies of political behavior—rational, critical, traditional, and skeptical—with rational and vital orientations emerging as the most prominent patterns thematically. These orientations reflect a reflective, moderate political stance shaped by minority experiences and sensitivity to identity-based politics. The study contributes to discussions on political behavior, identity politics, and minority participation in Indonesia’s local democracy.